2014
DOI: 10.1007/s12639-014-0517-4
|View full text |Cite
|
Sign up to set email alerts
|

Anticoccidial effects of herbal extracts on Eimeria tenella infection in broiler chickens: in vitro and in vivo study

Abstract: Safe alternative anticoccidial drug to chemical feed additives are herbal extracts, because they don't results to tissue residue and drug resistance. In order to evaluate the effects of herbal extracts to control avian coccidiosis, 180 one-day-old broiler chickens were randomly divided into nine equal groups, as follows: (1) Biarum bovei (2) Nectaroscordum tripedale( 3) Dorema aucheri (4) Cichorium intybus (5) Prangos ferulaceae (6) diclazuril (7) Artemisia absinthium (8) infected control (9) uninfected contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…The results of this investigation have demonstrated that the OP extracts have a noticeably destructive effect on Eimeria parasite. Previous investigations have used in vitro test to screen the anticoccidial effect of some plant compounds in broiler chickens [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this investigation have demonstrated that the OP extracts have a noticeably destructive effect on Eimeria parasite. Previous investigations have used in vitro test to screen the anticoccidial effect of some plant compounds in broiler chickens [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Plants produce a broad-spectrum variety of phytochemicals such as phenolics, polyacetylenes, alkaloids, polysaccharides, terpenoids, and essential oils with a large number of antimicrobial bioactivities [ 23 ]. Safe alternative to chemical anticoccidial drug is herbal products because they do not results to tissue residue and drug resistance [ 24 ]. The results of this study show the effectiveness of amprolium and madar for control of coccidiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, significant reduction in the mortality of birds infected with coccidiosis has been reported among different plant extracts (Drȃgan et al 2014;Gholamrezaie Sani et al 2013;Habibi et al 2016;Nghonjuyi et al 2015). The antimalaria 'artemisinin' derived from the herb Artemisia annua has been reported to have damaging effects on the macrogametocyte of E. tenella by limiting the expression of sarcoplasmic-endoplasmic reticulum calcium ATPase enzyme (del Cacho et al 2010).…”
Section: Control Measure Of Coccidiosismentioning
confidence: 94%